2014
DOI: 10.1371/journal.pone.0096483
|View full text |Cite
|
Sign up to set email alerts
|

The Position of DNA Cleavage by TALENs and Cell Synchronization Influences the Frequency of Gene Editing Directed by Single-Stranded Oligonucleotides

Abstract: With recent technological advances that enable DNA cleavage at specific sites in the human genome, it may now be possible to reverse inborn errors, thereby correcting a mutation, at levels that could have an impact in a clinical setting. We have been developing gene editing, using single-stranded DNA oligonucleotides (ssODNs), as a tool to direct site specific single base changes. Successful application of this technique has been demonstrated in many systems ranging from bacteria to human (ES and somatic) cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 45 publications
5
20
1
Order By: Relevance
“…This specific combination of CRISPR/Cas9 and ssODN has been shown previously to be optimal for RGEN-directed correction [14]. In the experiments reported herein, we utilize the 72NT oligonucleotide since previous data have established that targeting the non-transcribed strand at this ssODN length leads to a higher level of gene editing [31]. In addition, the use of the complementary oligonucleotide, targeting the transcribed strand, leads to artefactual annealing to the sgRNA component of the CRISPR/Cas9 complex, reducing overall activity [14].…”
Section: Resultsmentioning
confidence: 99%
“…This specific combination of CRISPR/Cas9 and ssODN has been shown previously to be optimal for RGEN-directed correction [14]. In the experiments reported herein, we utilize the 72NT oligonucleotide since previous data have established that targeting the non-transcribed strand at this ssODN length leads to a higher level of gene editing [31]. In addition, the use of the complementary oligonucleotide, targeting the transcribed strand, leads to artefactual annealing to the sgRNA component of the CRISPR/Cas9 complex, reducing overall activity [14].…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of the corrective change depends on several of factors (i.e., the length of the ssODN, the proliferative cell cycle, and the presence of DNA breaks in the host genome) [29, 30]. Recently, a single base change on the genome has been achieved through a combined use of the TALEN and ssODN templates [16, 17]. In the present study, we applied the TALEN protein delivery system for a specific base change in two systems (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, a significant challenge of this method is the low efficiency, requiring the use of a selection marker or screening a large number of subclones [15]. Recently, precise genome editing was achieved through a combined use of the TALEN and single‐stranded oligonucleotide DNA (ssODN) templates [16, 17]. In the present study, we combined the method of bacterial T3SS‐mediated TALEN protein injection and ssODN template transfection, providing an effective alternative method for precise DNA modification in stem cells.…”
Section: Introductionmentioning
confidence: 99%
“…A number of laboratories reported that treatment of cells with anticancer drugs such as camptothecin, which induces double‐strand breaks in chromosomal DNA, elevates the frequency of gene editing directed by ssODNs (Ferrara and Kmiec, ; Ferrara et al ., ; Olsen et al ., ; Storici et al ., ; Wang et al ., ). In effect, these drugs were used as adjuvants, pretreating cells prior to the addition of oligonucleotides and thereby elevating the number of gene repair events in a particular cell.…”
Section: Dna Damage and Dna Replication In Gene Editingmentioning
confidence: 97%